Racial and ethnic differences in predictors of vitamin D among pregnant women in south-eastern USA. (28th February 2019) - Chawla, Devika; Daniels, Julie L.; Benjamin-Neelon, Sara E.; Fuemmeler, Bernard F.; Hoyo, Cathrine; Buckley, Jessie P.
Abstract: Insufficient vitamin D during pregnancy increases risk of adverse outcomes, with known differences by race/ethnicity. We sought to determine whether predictors of vitamin D insufficiency vary by race/ethnicity in an ethnically diverse pregnancy cohort. Plasma 25-hydroxyvitamin D concentrations and patient characteristics were measured at first prenatal visit to prenatal clinics in south-eastern USA between 2009 and 2011 ( n 504). Prevalence ratios (PR) and 95 % CI were estimated using multivariable regression to quantify predictors of vitamin D insufficiency, overall and by race/ethnicity. In race/ethnicity-stratified models, season was most associated with vitamin D insufficiency among non-Hispanic white women; PR for winter v. summer were 3·58 (95 % CI 1·64, 7·81) for non-Hispanic white, 1·52 (95 % CI 1·18, 1·95) for Hispanic and 1·14 (95 % CI 0·99, 1·30) for non-Hispanic black women. Although women with darker skin tones are most vulnerable to prenatal vitamin D insufficiency, season may be more strongly associated with insufficiency among women with lighter skin tones.